Ética profesional y su incidencia en el ámbito laboral de las secretarias del Departamento de Talento Humano de la Unidad Educativa del Milenio: Carlos Alberto Aguirre Avilés de la Parroquia La Unión - Mora Zambrano, Génesis Michell (2022)
This case study focuses on professional ethics and its impact on the workplace of the secretaries of the human talent department of the educational unit of the millennium: "Carlos Alberto Aguirre Aviles" of the La Unión parish whose proposed objective is based on professional ethics as a main actor in the professional development of the secretary. Recognizing ethics as the set of norms supported and accepted by a large part of society, which together with work represents a commitment not only with oneself but with the employer, responsibility and respect are highlighted as guides to the values that derive from the ethics. In the secretarial field, knowledge about professional ethics should be mandatory due to the role it plays within the institutions, since they function as links between the processes that constitute it. The secretaries of the educational unit demonstrate correct values and their interpersonal relationship is good, however they are not clear about what professional ethics respects due to the lack of training by the institution.